2012
DOI: 10.1155/2012/713203
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of Chemically Etched Nanoporous Silicon Embedded in Sol‐Gel Matrix

Abstract: Nanoporous (NPs) silicon fabricated by chemical etching process in HF acid was first separated in tetrahydrofuran (THF) solvent and then incorporated into SiO2matrix. The matrix was prepared by sol gel process in which dimethylformamide (DMF) was used as drying chemical control additive (DCCA) to form crack-free dried sample. We examined the optical properties of NPs in three medium which are solvent, sol, and dried sol gel. Our observations reveal that absorption spectra of NPs silicon in THF are modified wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Therefore, 355 nm excitation wavelength was selected for all samples in order to understand the PL behavior of Psi corresponding to the quantity of wafer piece. Recently our group reported that the emission spectra of Psi in THF and dioxane using 4 wafer pieces also [22,23]. Weak emissions lights were obtained from the Psi doped sol gel prepared using 4 quantities of silicon wafer piece.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 355 nm excitation wavelength was selected for all samples in order to understand the PL behavior of Psi corresponding to the quantity of wafer piece. Recently our group reported that the emission spectra of Psi in THF and dioxane using 4 wafer pieces also [22,23]. Weak emissions lights were obtained from the Psi doped sol gel prepared using 4 quantities of silicon wafer piece.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Because, demonstration of Psi/nc-Si in sol gel is easily manageable, that enables the fabrication of samples with high densities of silicon nanoparticles for optoelectronics purposes. Due to being greatly important to optical stability of Psi/nc-Si within sol gel matrix in view of light stimulation, recently systematic studies were done by our group especially on PL and structural properties of the NCs powder [20,21], nanoporous silicon [22,23] in sol gel host. Although porous silicon could stabilize in the sol gel active medium, weak emission and spontaneous signals were obtained due to low concentration of Psi colloidal solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of DGEBA to GPMS reduces the hydrolysis or alcoholysis of epoxy rings during the hydrolytic condensation [12]. The hydrolytic condensation led to soluble products, despite the use of significant amounts of TEOS [22], due to the network blocking characteristics of the GPMS and MPMS monomers (they are trifunctional monomers while TEOS is a tetrafunctional monomer), and the low water to silicon ratio (1:1) used [23]. The large fraction of intramolecular cycles produced in these polymerizations also favours the generation of soluble products [12,[16][17][18].…”
Section: Preparation Of Compositesmentioning
confidence: 99%
“…It is well-known that hydrogen bonding plays an important role in the self-assembly process of organogels [25][26][27]. At present, in order to further clarify this and investigate the effect of many factors on assembly, we have measured the FT-IR spectra of all xerogels, as shown in Figure 4.…”
Section: Morphological Investigation Of Organogelsmentioning
confidence: 99%